Archeologia a Firenze : città e territorio : Atti Del Workshop, Firenze, 12-13 Aprile 2013 - D'Aquino, Valeria,; Guarducci, Guido,; Nencetti, Silvia,; Valentini, Stefano (Archaeologist), (Archaeopress archaeology., 2015)
This volume presents the proceedings of the workshop 'Archeologia a Firenze: Città e Territorio', organized by CAMNES, Centre for Ancient Mediterranean and Near Eastern Studies, in collaboration with the Soprintendenza per i Beni Archeologici della Toscana, in April 2013.